Pandangan Masyarakat Terhadap Pengobatan dengan Bantuan Buaya Mistik di Desa Kuala Pembuang Kecamatan Seruyan Hilir Kabupaten Seruyan - Al Qiram, Tahfiz; Effendi, Rusdi; Hairiyadi, Hairiyadi (Prabayaksa: Journal of History Education, 2021)
At the beginning of the 21st century, the people of Kuala Pembuang still believed in the existence of intermediaries who gave offerings to mystical crocodiles in the midst of the rise of science and technology, one of which was health. The purpose of this study was to determine the public's view of treatment with the help of crocodiles (mystical). The initial stage of this research is data collection through literature study and field studies. Literature study is used to obtain written data in the form of books or obtain primary data directly. Furthermore, after the data is collected the data is again considered to see the validity of the source. The next stage of interpretation is to describe the sources that have been considered. Finally, the historiography part is processing the data into written form. The results showed that the treatment through the ritual of giving offerings to the crocodile care family (mystical) was carried out through several stages and the community's view of the ritual procession still believed and some did not believe in the treatment process through the procession. the ritual of giving offerings. The conclusion from the research results is that the ritual of giving offerings to crocodiles (mystical) in order to cure the disease can only be done if the sick person has blood ties with the owner of the mystical crocodile and this ritual is only done if there is a family affected by the disease and it is believed that they cannot recover. in a way obstructed through the help of a doctor. In this case, people also have different opinions in dealing with treatment through these rituals there work as fishermen.